Strategi Komunikasi Organisasi Aisyiyah dalam Meningkatkan Aktivitas Dakwah Pengurus di Ranting Medan Marelan - Lubis, Mia Rafiqa M; Elfi Yanti Ritonga (PAI RAFAH, 2024)
The purpose of this research is to find out the communication approach used by the da'wah development organization in Aisyiyah Ranting Medan Marelan, as well as the management of da'wah development itself. This research was conducted in Medan city using a qualitative approach and descriptive research methodology. The data collection methods used include interviews, observation, literature study, and documentation. The research was conducted by interviewing Aisyiyah administrators with diverse backgrounds, including students, teachers (mubaligh), and housewives, to understand their strategies in enhancing da'wah activities. The research findings show the impact of Aisyiyah in enhancing da'wah efforts in Aisyiyah Ranting Medan Marelan. Observations and interviews show that Aisyiyah's management effectively applies strategic management, which involves planning and supervising the organization to achieve its vision, mission, goals and objectives. This approach successfully integrates various aspects of women's and children's lives into Aisyiyah's activities. Relevant documentary evidence supporting this research also indicates a substantial improvement in Aisyiyah's proselytization efforts in Medan Marelan. The descriptive data analysis method used facilitates the transformation of unprocessed data into a format that can be understood and interpreted.